The roles of Islamic financial technology (FINTECH) in fostering financial inclusion in Malaysia / Nurul’ain Mohd ... [et al.] - Mohd, Nurul’ain; Razali, Mastura; Yahaya, Muhammad Hasif; Baharuddin, Zainur Nadiyah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
The financial sector is undergoing a paradigm shift due to technological improvements. As a result of these technical breakthroughs, the financial industry has experienced a significant transformation, characterised by a growing reliance on technology and the emergence of several opportunities and barriers. Thus, by examining official reports and the central bank’s website, the research aimed to analyse the roles played by Islamic fintech in promoting financial inclusion to gain a comprehensive understanding of fintech in Malaysia. The qualitative analytical approach employed in this study relies upon a wide range of sources, such as the Central Bank of Malaysia Financial Inclusion Framework 2023-2026, official papers on fintech, the Bank Negara Malaysia website, and pertinent journal articles. The findings indicated that the Islamic fintech sector in Malaysia has prioritised the empowerment of small and medium-sized firms, unbank population, marginalised communities, and vulnerable sectors to encourage financial inclusion in Malaysia. This approach is designed to stimulate economic growth and act as an intermediary for the progress of the digital economy through the provision of financial services accessibility.